Time pressure, employee well-being, perceived organizational support and turnover intention of information technology executives in Malaysia: A proposed conceptual framework - Langove, N. (American Scientific Publishers, 2015)
Globalization stimulates the role of information technology (IT) among emerging market and creates new challenges for organizations to be competitive to survive in the market. These challenges alter and threaten the capability of employees in their working environment. Time pressure is regarded as one of key factors which negatively contribute to the employee turnover among IT Executives in Software Companies. This study in response to this issue aims to examine the impact of time pressure on well-being and turnover intention with the moderating role of perceived organizational support. This study is based on a conceptual framework and the data will be collected to observe the relationship between time pressure, employee well-being, perceived organizational support and turnover intention with the help of structural equation modeling. To the best knowledge of researcher, none of the study has found out the time pressure with the mediating variable of employee well-being and moderating variable of perceived organizational support. Â© 2015 American Scientific Publishers. All rights reserved.